A health partnership to reduce neonatal mortality in four hospitals in Rwanda - Placide Ntigurirwa; Kathy Mellor; Daniel Langer; Mari Evans; Emily Robertson; Lisine Tuyisenge; Alan Groves; Tom Lissauer (BMC, 2017)
Abstract Background A health partnership to improve hospital based neonatal care in Rwanda to reduce neonatal mortality was requested by the Rwandan Ministry of Health. Although many health system improvements have been made, there is a severe shortage of health professionals with neonatal training. Methods Following a needs assessment, a health partnership grant for 2 years was obtained. A team of volunteer neonatologists and paediatricians, neonatal nurses, lactation consultants and technicians with experience in Rwanda or low-income countries was assembled. A neonatal training program was provided in four hospitals (the 2 University hospitals and 2 district hospitals), which focused on nutrition, provision of basic respiratory support with nasal CPAP (Continuous Positive Airway Pressure), enhanced record keeping, thermoregulation, vital signs monitoring and infection control. To identify if care delivery improved, audits of nutritional support, CPAP use and its complications, and documentation in newly developed neonatal medical records were conducted. Mortality data of neonatal admissions was obtained. Results Intensive neonatal training was provided on 27 short-term visits by 10 specialist health professionals. In addition, a paediatric doctor spent 3 months and two spent 6 months each providing training. A total of 472 training days was conducted in the neonatal units. For nutritional support, significant improvements were demonstrated in reduction in time to initiation of enteral feeds and to achieve full milk feeds, in reduction in maximum postnatal weight loss, but not in days for regaining birth weight. Respiratory support with bubble CPAP was applied to 365 infants in the first 18 months. There were no significant technical problems, but tissue damage, usually transient, to the nose and face was recorded in 13%. New medical records improved documentation by doctors, but nursing staff were reluctant to use them. Mortality for University teaching hospital admissions was reduced from 23.6% in the 18 months before the project to 21.7%. For the two district hospitals, mortality reduced from 10% to 8.1%. A major barrier to training and improved care was low number of nurses working on neonatal units and staff turnover. Conclusion This health partnership delivered an intensive program of capacity building by volunteer specialists. Improved care and documentation were demonstrated. CPAP was successfully introduced. Mortality was reduced. This format can be adapted for further training and improvement programs to improve the quality of facility-based care.